Lung cancer treatment patterns and factors relating to systemic therapy use in Australia. Issue 5 (12th July 2021) - Ngo, Preston; Goldsbury, David E.; Karikios, Deme; Yap, Sarsha; Yap, Mei Ling; Egger, Sam; O'Connell, Dianne L.; Ball, David; Fong, Kwun M.; Pavlakis, Nick; Rankin, Nicole M.; Vinod, Shalini; et al.
Abstract: Aim: Systemic therapies for lung cancer are rapidly evolving. This study aimed to describe lung cancer treatment patterns in New South Wales, Australia, prior to the introduction of immunotherapy and latest‐generation targeted therapies. Methods: Systemic therapy utilization and treatment‐related factors were examined for participants in the New South Wales 45 and Up Study with incident lung cancer ascertained by record linkage to the New South Wales Cancer Registry (2006–2013). Systemic therapy receipt to June 2016 was determined using medical and pharmaceutical claims data from Services Australia, and in‐patient hospital records. Factors related to treatment were identified using competing risks regressions. Results: A total of 1, 116 lung cancer cases were identified with a mean age at diagnosis of 72 years and median survival of 10.6 months. Systemic therapy was received by 45% of cases. Among 400 cases with metastatic non–small cell lung cancer, 51% and 28% received first‐ and second‐line systemic therapy, respectively. Among 112 diagnosed with small‐cell lung cancer, 79% and 29% received first‐ and second‐line systemic therapy. The incidence of systemic therapy was lower for participants with indicators of poor performance status, lower educational attainment, and those who lived in areas of socioeconomic disadvantage; and was higher for participants with small‐cell lung cancer histology or higher body mass index. Conclusion: This population‐based Australian study identified patterns of systemic therapy use for lung cancer, particularly small‐cell lung cancer. Despite a universal healthcare system, the analysis revealed socioeconomic disparities in health service utilization and relatively low utilization of systemic therapy overall. Abstract : Systemic therapy for lung cancer participants in the 45 and Up Study (2006–2009; Australia) was relatively low, received by 45% of those with NSCLC and 79% with SCLC. Multivariable regressions found that treatment was more likely for participants who were healthy, had high SES, high BMI, and had SCLC. Competing risks regressions found that SES disparities in care were not explained by differences in mortality.